Lessons from Empirical Models of Exchange Rates : Volume 34 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1987)
This paper finds scope for some optimism that the empirical modeling of exchange rates will someday lead to significantly better-than-random explanations. The first part of the paper focuses on the relationships among exchange rates, national price levels, interest rates, and international balances of payments and provides perspectives on some elements of truth about these relationships that are consistent with the past decade of modeling failures. The lessons emphasize the importance of analyzing exchange rates within complete macroeconomic frameworks and of assuming that expectations are formed in ways consistent with the structural models or with information that can be easily extracted from time series of relevant variables. The open issues include the questions of whether it is adequate or appropriate to treat assets as perfect substitutes or, equivalently, to use the uncovered interest rate parity hypothesis. To the extent that efforts are devoted to modeling exchange rates in general equilibrium frameworks that do not treat assets as perfect substitutes, a second open issue is how to distinguish assets and to specify a basis for portfolio preferences that has solid microeconomic foundations.